2019
DOI: 10.1126/science.aaw6378
|View full text |Cite
|
Sign up to set email alerts
|

Imaging covalent bond formation by H atom scattering from graphene

Abstract: Viewing the atomic-scale motion and energy dissipation pathways involved in forming a covalent bond is a longstanding challenge for chemistry. We performed scattering experiments of H atoms from graphene and observed a bimodal translational energy loss distribution. Using accurate first-principles dynamics simulations, we show that the quasi-elastic channel involves scattering through the physisorption well where collision sites are near the centers of the six-membered C-rings. The second channel results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
156
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(168 citation statements)
references
References 66 publications
(81 reference statements)
12
156
0
Order By: Relevance
“…Next, we discuss a possible reason for the less satisfactory performance of RPMD at Ei =0.6~1.0 eV. Indeed, similar phenomenon has been observed in recent NE-RPMD calculations for H scattering on graphene 29 , where the RPMD calculated sticking probabilities at high incidence energies are also generally lower than classical ones (note that there is no internal state and ZPE for hydrogen atom). These authors offered no explanation for this difference in that work.…”
Section: Additional Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Next, we discuss a possible reason for the less satisfactory performance of RPMD at Ei =0.6~1.0 eV. Indeed, similar phenomenon has been observed in recent NE-RPMD calculations for H scattering on graphene 29 , where the RPMD calculated sticking probabilities at high incidence energies are also generally lower than classical ones (note that there is no internal state and ZPE for hydrogen atom). These authors offered no explanation for this difference in that work.…”
Section: Additional Resultssupporting
confidence: 71%
“…This procedure not only correctly samples the Boltzmann weight in the correlation function, but also ensures that each new NVE trajectory explores a different region of microcanonical phase space 11 . Although originally proposed for calculating correlation functions, this procedure has been successfully used in recent direct dynamics simulations 15,29 , giving rise to the proper initial conditions for NVE dynamics calculations. To check this ability, we plot in Fig.…”
Section: Additional Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other work, it was shown that weak molecular bonds can form at the EDL interface, and nominal activation and deactivation energies can be used to control the molecular bonding between the ions and the substrate [23]. Furthermore, scattering experiments with hydrogen and graphene showed that hydrogen atoms possess a high sticking probability with graphene: C-H bonds formed within 10fs of interaction time [24]. Both of these studies support the notion of electrochemically generating ions within the liquid dielectric, providing an activation energy via electric field to form weak molecular bonds with graphene, and providing a deactivation energy to remove those molecular bonds.…”
Section: A Transfer Characteristics and Operationmentioning
confidence: 98%